Analisis Pemanfaatan E-Government di Kantor Lurah Guntung Kecamatan Bontang Utara Kota Bontang - Suci Azizah Febriyani; Muhammad Hairul Saleh; Jauchar Berlian (Jurnal Ilmu Pemerintahan, 2022)
This study aims to analyze and describe the forms of e-government utilization at the Guntung Lurah Office, analyze and describe the use of e-government in facilitating the work of employees at the Guntung Lurah Office and identify the driving factors and inhibiting factors for the use of e-government at the Guntung Lurah Office. The type of research used is descriptive qualitative. The data collection technique used was library research and field research using observation, interviews and documents. In this study using data analysis developed by Miles and Huberman. The results of the study show that the use of e-government in the Guntung Lurah Office has various forms of use in various fields, namely there are seven forms of e-government, the use of e-government in facilitating the work of employees seen from indicators of efficiency, effectiveness and transparency has been fulfilled. For the driving factors seen from the successful elements of e-government development, namely support/support, capacity/ability, value/benefits, and local culture/local culture to produce supporting elements so that e-government can be implemented. However, in the implementation, there are still obstacles that hinder the use of e-government, such as the internet network which plays an important role, in fact it is still experiencing problems, the lack of socialization carried out to the public in the field of services and application development has not been carried out optimally.